Mental Health Integrated Service Post (Posyandu Jiwa): A Community-Based Response to the Increasing Number of People with Mental Disorders (ODGJ) in Bacem Village, Ponggok, Blitar - Burhani, Syaechul (Journal of Educational Research and Practice, 2023)
Posyandu Jiwa is a special posyandu for people with mental disorders. The purpose of this research was to find out the role of Posyandu Jiwa in the process of healing and empowering people with mental disorders (ODGJ). The subjects of this study were ODGJ, Posyandu Jiwa cadres, and the community involved in Posyandu Jiwa activities. based on the topic, the method used is a qualitative method using a case study approach. The research was conducted by interviewing related parties, observing Posyandu Jiwa activities, and documentation. The place of this research is located in the Posyandu Jiwa work area, namely in Bacem Village, Ponggok District, Blitar Regency. The time of the research was carried out when the posyandu activities were carried out. The results showed that the individuals involved in social interaction were Posyandu Jiwa and ODGJ cadres. behavior that appears in social interactions, activities held by Posyandu Jiwa. individual position in the Posyandu Jiwa, the cadres have their respective duties and responsibilities, while the ODGJ are patients of the Posyandu Jiwa. the relationship between individuals and behavior, cadres play a role in holding posyandu activities and ODGJ participate in a series of activities. Posyandu Jiwa helps the healing process of ODGJ which can last for years. Empowerment that is carried out can help the economy of ODGJ. The empowerment that is often done is to draw pictures which are exhibited at national exhibitions and applied to t-shirts to be traded.